Studien über die atmosphärische Zirkulation in der letzten Eiszeit - Flohn, Hermann (ERDKUNDE, 1953)
The discussion of the climate during the glacial period is now being considered from a meteorological aspect. Looking at the general air circulation during the initial stages and the climax of the glacial period we find that the glacial anticyclones played quantitatively a minor role. For the tropical and subtropical zones there is proof of a general decrease in temperature of about 4° C. The areas close to the ice experienced pronounced temperature inversions near the ground. It is possible to give an approximate estimate of the average distribution of the winds, temperature and precipitation in Southern Germany during the glacial period. The total amount of evaporation (and consequently also of precipitation) was at least 20 per cent, less than today. The cause of the glacial periods may most likely be seen in changes of solar activity in single parts of the spectrum (as suggested by Huntington and Willett) since the actual climatic anomalies connected with these changes show the same distribution as those of the glacial period.